Yielding nature and Hall-Petch relationships in Ti-6Al-4V alloy with fully equiaxed and bimodal microstructures. (November 2019) - Chong, Yan; Deng, Guanyu; Gao, Si; Yi, Jangho; Shibata, Akinobu; Tsuji, Nobuhiro
Abstract: Hall-Petch relationships were studied in Ti-6Al-4V alloy with fully equiaxed and two different bimodal microstructures obtained by intercritical annealing at 850 °C (BM850) and 950 °C (BM950). The Hall-Petch coefficient of the BM850 microstructure composed of harder primary α grains and softer transformed β areas was identical to that of the fully equiaxed microstructure, indicating the same nature of yielding behavior determined by the resisting ability of equiaxed α grain boundaries against slip transfer in both microstructures. The BM950 microstructure having smaller amount of primary α, however, showed a yielding nature like a particle-strengthened composite, leading to the different Hall-Petch relationship. Graphical abstract: Unlabelled Image